Jesus e o sábado - Lemos, Cláudia Teresinha (2011)
The present work intends to investigate the sabbath in the bible and the implications it brought to God s people. We are also going to study Jesus s words related to it, considering the great relevance the day had to Him, as a Jew. The first chapter explores the sabbath in the Old Testament, since there is no way to understand the significance the jewish people dedicated to this day, in Jesus s times, without understanding what it represented previously to them. We are going to include in the same chapter a brief study on Creationism, because we think the background to understand the sabbath roots are in the creation week , according to the Genesis account. In the second chapter, we are going to analyze some verses taken from The Gospel of Mark, in which Mark reports to us a controversy between Jesus and the Pharisees, because of the sabbath. We are going to conclude with the theological meaning of the sabbath, its implications and consequences in Jesus s times and still in our times.